Polyalkynes capped by sulfur and selenium - Werz, Daniel B.; Gleiter, Rolf (The journal of organic chemistry, 2003)
The synthesis of sulfur- and selenium-capped polyalkynes with two to four triple bonds was achieved. As starting materials the bis(trimethylsilyl)-protected polyalkynes were used, which were treated with MeLi/LiBr. The reaction of the resulting lithium salts with thiocyanatomethane and selenium/methyl iodide afforded 2(n) and 3(n), respectively. Spectroscopic (PE and UV) and quantum chemical investigations show significant interaction between the chalcogen atoms. The structure of 3(4) was investigated in the solid state, showing relatively short intermolecular Se···Se interactions.